Effects of natural polyphenol-rich pomegranate juice on the acute and delayed response of Homocysteine and steroidal hormones following weightlifting exercises: a double-blind, placebo-controlled trial - Ammar, A.; Turki, M.; Trabelsi, K.; Bragazzi, N. L.; Boukhris, O.; Bouaziz, M.; Ayadi, F.; El Abed, K.; Driss, T.; Souissi, N.; Chtourou, H.; Bailey, S. J.; et al. (Journal of the International Society of Sports Nutrition, 2020)
Background: Maximal strength-speed exercise is a powerful stimulus to acutely increase concentrations of circulating steroid hormones and homocysteine [Hcy]. There is some evidence that antioxidant beverages rich in polyphenols can attenuate [Hcy] levels and modulate endocrine responses in favor of an anabolic environment. Polyphenols-rich pomegranate (POM) have been reported to possess one of the highest antioxidant capacities compared to other purported nutraceuticals and other food stuffs. Studies focused on proving the beneficial effect of POM consumption during maximal strength exercises have only measured physical performance, muscle damage, oxidative stress and inflammatory responses, while POM effects on [Hcy] and hormonal adaptations are lacking. The aim of the present study was to investigate the effect of consuming natural polyphenol-rich pomegranate juice (POMj) on the acute and delayed [Hcy] and steroidal hormonal responses to a weightlifting exercises session. Methods: Nine elite weightlifters (21.0 ± 1 years) performed two Olympic-weightlifting sessions after ingesting either the placebo (PLA) or POMj supplements. Venous blood samples were collected at rest and 3 min and 48 h after each session. Results: Compared to baseline values, circulating cortisol [C] decreased (p < 0.01) and testosterone/cortisol [T/C] ratio increased immediately following the training session in both PLA and POMj conditions (p = 0.003 for PLA and p = 0.02 for POM). During the 48 h recovery period, all tested parameters were shown to recover to baseline values in both conditions with significant increases in [C] and decreases in [T/C] (p < 0.01 for PLA and p < 0.05 for POMj) from 3 min to 48 h post-exercises. Compared to PLA, a lower level of plasma testosterone [T] was registered 3 min post exercise using POMj supplementation (p = 0.012) and a significant decrease (p = 0.04, %change = - 14%) in plasma [Hcy] was registered during the 48 h recovery period only using POMj. A moderate correlation was observed between [Hcy] and [T] responses (p = 0.002, r = - 0.50). Conclusion: In conclusion, supplementation with POMj has the potential to attenuate the acute plasma [T] response, but did not effect 48 h recovery kinetics of [Hcy] following weightlifting exercise. Further studies investigating androgen levels in both plasma and muscular tissue are needed to resolve the functional consequences of the observed acute POMj effect on plasma [T].